Designing A Strategic Quality Assurance Framework In Education: Insights From ISO 21001:2018 Implementation - Moh Khoirul Anam; Agus Zaenul Fitri; As’aril Muhajir (International Journal of Interdisciplinary Research, 2025)
This paper explores the strategic development and implementation of a quality assurance (QA) framework in the educational sector, grounded in the ISO 21001:2018 standard. As a specialized management system for educational organizations, ISO 21001:2018 provides a structured approach to enhancing the effectiveness and efficiency of educational processes. The standard emphasizes alignment between institutional operations and the expectations of learners, educators, and other relevant stakeholders. Through a qualitative library research methodology, this study reviews and synthesizes academic literature, policy documents, and institutional case studies that discuss the application of ISO 21001:2018 within various educational settings. The core principles of the standard stakeholder-centered management, strong leadership, engagement of people, process-oriented strategies, continuous improvement, and evidence-based decision-making are examined and incorporated into the design of a strategic QA framework suitable for educational institutions of different types and scales. The findings reveal that implementing a QA system based on ISO 21001:2018 fosters institutional accountability, promotes systematic performance monitoring, and ensures continuous feedback loops for educational improvement. The proposed framework encourages educational organizations to integrate quality planning into strategic decision-making and to align their mission, vision, and educational goals with globally recognized quality benchmarks. Adopting ISO 21001:2018 as the foundation for quality assurance not only strengthens institutional governance but also significantly contributes to better learning outcomes, stakeholder satisfaction, and long-term sustainability. This study recommends that educational institutions consider ISO 21001:2018 not merely as a compliance tool but as a strategic asset for quality transformation.